Separator for electrochemical device and electrochemical device including the same

By using porous coatings formed by polyimide modified metal-organic framework particles and polymer binder in the separator of the lithium secondary battery, gas generated by decomposition of electrolyte liquid is adsorbed, and the performance deterioration and safety risks caused by gas generation in the lithium secondary battery are solved, and the effect of extending battery life and improving safety is achieved.

CN119948687APending Publication Date: 2025-05-06LG ENERGY SOLUTION LTD +1
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202480004139.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-04-13
Filing Date
2024-04-09
Publication Date
2025-05-06

AI Technical Summary

Technical Problem

Lithium secondary batteries may produce gas during storage or operation, resulting in increased internal resistance, shortened life, and may even cause ignition or explosion.

Method used

A separator for an electrochemical device is provided, including a porous polymer substrate and a porous coating comprising a polyimide modified first metal-organic framework particles, a second metal-organic framework particles and a polymer binder for adsorbing gases generated by the decomposition of the electrolyte liquid.

Benefits of technology

By adsorbing gases generated by decomposition of electrolyte liquids, preventing the performance of electrochemical devices caused by gases, prolonging battery life, and reducing the risk of ignition or explosion.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005326423140000181
    Figure BDA0005326423140000181
Patent Text Reader

Abstract

The present disclosure provides a separator for an electrochemical device, the separator comprising: a porous polymer substrate; and a porous coating layer comprising polyimide-modified first metal-organic framework (MOF) particles, second metal-organic framework particles, and a polymer binder, and formed on at least one surface of the porous polymer substrate, wherein at least one of the first metal-organic framework particles and the second metal-organic framework particles contains zirconium and has an amine group introduced therein.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application claims priority to and the benefit of Korean Patent Application No. 10-2023-0048993 filed in the Korean Intellectual Property Office on April 13, 2023, the entire contents of which are incorporated herein by reference.

[0002] The present disclosure relates to a separator for an electrochemical device and an electrochemical device including the same. Background Art

[0003] Electrochemical devices convert chemical energy into electrical energy using electrochemical reactions, and recently, lithium secondary batteries, which have high energy density and voltage, long cycle life, and are applicable in a variety of fields, have been widely used. The lithium secondary battery may include an electrode assembly prepared with a positive electrode, a negative electrode, and a separator disposed between the positive electrode and the negative electrode, and may be manufactured by storing the electrode assembly in a case together with an electrolyte liquid.

[0004] When abnormal operation occurs during the storage or operation of lithium secondary batteries due to internal short circuits, overcharging, exposure to temperatures higher than the operating temperature, etc., gas may be generated while the electrolyte liquid contained in the lithium secondary battery is decomposed. The gas generated in the battery may cause the internal resistance of the battery to increase, shortening the battery life. When the amount of gas generated is large, deformation may occur in the battery housing or internal structure, causing the battery to catch fire or explode. Therefore, research on methods for reducing the amount of gas generated or reducing the volume expansion of the battery caused by gas has been conducted. Summary of the invention

[0005] Technical issues

[0006] The present disclosure aims to provide a separator for an electrochemical device capable of adsorbing a gas generated in the electrochemical device, and an electrochemical device including the same.

[0007] Technical Solution

[0008] One aspect of the present disclosure provides a separator for an electrochemical device, the separator comprising: a porous polymer substrate; and a porous coating, the porous coating comprising first metal-organic framework (MOF) particles modified by polyimide, second metal-organic framework particles and a polymer binder, and formed on at least one surface of the porous polymer substrate, wherein at least one of the first metal-organic framework particles and the second metal-organic framework particles comprises zirconium (Zr) and has amine groups introduced therein.

[0009] The average particle size (D) of the first metal-organic framework particles and the second metal-organic framework particles according to particle size distribution (PSD) analysis 50 ) can each be 300 nm or more and 10 μm or less.

[0010] The average pore size of the first metal-organic framework particles and the second metal-organic framework particles may each be greater than 5 nm and less than 200 nm.

[0011] The pore volumes per unit mass of the first metal-organic framework particles and the second metal-organic framework particles may each be 0.2 cm 3 / g or more and 1.0cm 3 / g or less.

[0012] The first metal-organic framework particles and the second metal-organic framework particles may each independently be selected from UiO-66-NH2, UiO-67-NH2, NU-1002-NH2, and MOF-808-NH2.

[0013] The first metal-organic framework particles and the second metal-organic framework particles may be included in a weight ratio of 35:65 to 45:55.

[0014] The metal-organic framework particles and the polymer binder may be included in a weight ratio of 80:20 to 95:5.

[0015] Another aspect of the present disclosure provides an electrochemical device including: a positive electrode; a negative electrode; and a separator disposed between the positive electrode and the negative electrode, wherein the separator is a separator for an electrochemical device according to one aspect.

[0016] The electrochemical device may be a lithium secondary battery.

[0017] Beneficial Effects

[0018] The separator for an electrochemical device according to the present disclosure can adsorb gas such as carbon dioxide generated by decomposition of an electrolyte liquid in a coating layer, thereby preventing performance degradation of an electrochemical device caused by the gas. DETAILED DESCRIPTION

[0019] Hereinafter, each constituent element of the present disclosure will be described in more detail so that those skilled in the art can easily implement the present disclosure, however, this is only an example, and the right scope of the present disclosure is not limited to the following description.

[0020] The terms "include / comprising" used in this specification are used to list materials, compositions, devices and methods useful for the present disclosure, and are not limited to the listed examples.

[0021] The terms "about" and "substantially" used in this specification are used to refer to a range of values ​​or degrees or as a meaning close thereto in view of unique manufacturing and material tolerances, and are used to prevent infringers from improperly using the disclosure that states precise or absolute numbers provided to aid understanding of the disclosure.

[0022] The "electrochemical device" used in this specification may mean a primary battery, a secondary battery, a supercapacitor, or the like.

[0023] One embodiment of the present disclosure provides a separator for an electrochemical device, the separator comprising: a porous polymer substrate; and a porous coating, the porous coating comprising first metal-organic framework (MOF) particles modified by polyimide, second metal-organic framework particles and a polymer binder, and formed on at least one surface of the porous polymer substrate, wherein at least one of the first metal-organic framework particles and the second metal-organic framework particles comprises zirconium (Zr) and has amine groups introduced therein.

[0024] The porous polymer substrate is a porous film formed with a plurality of pores, and can prevent short circuits by electrically insulating the positive electrode and the negative electrode. For example, when the electrochemical device is a lithium secondary battery, the porous polymer substrate can be an ion-conducting barrier that allows lithium ions to pass through while preventing electrical contact between the positive electrode and the negative electrode. At least some of the pores can form a three-dimensional network connecting the surface and the interior of the porous polymer substrate, and a fluid can pass through the porous polymer substrate through the pores.

[0025] As a porous polymer substrate, a material that is physically and chemically stable to electrolyte liquids and organic solvents can be used. Examples of porous polymer substrates may include resins, such as polyolefins (such as polyethylene, polypropylene and polybutylene), polyvinyl chloride, polyethylene terephthalate, polycycloolefins, polyether sulfones, polyamides, polyimides, polyimide amides, nylons, polytetrafluoroethylene, and copolymers or mixtures thereof, but are not limited thereto. Preferably, polyolefin-based resins can be used. Polyolefin-based resins can be processed into relatively thin, and can allow coating slurries to be easily coated thereon, and are therefore suitable for manufacturing electrochemical devices with higher energy density.

[0026] The porous polymer substrate may have a monolayer or multilayer structure. The porous polymer substrate includes two or more polymer resin layers with different melting points (Tm), and can provide a shutdown function during battery runaway at high temperatures. For example, the porous polymer substrate may include a polypropylene layer with a relatively high melting point and a polyethylene layer with a relatively low melting point. Preferably, the porous polymer substrate may have a three-layer structure in which polypropylene, polyethylene and polypropylene are laminated in this order. Since the polyethylene layer melts as the battery temperature rises to a temperature higher than a predetermined temperature, the pores are closed, and thermal runaway of the battery can be prevented.

[0027] The thickness of the porous polymer substrate may be 1 μm or more and 100 μm or less. Specifically, the thickness of the porous polymer substrate may be 10 μm or more and 90 μm or less, 20 μm or more and 80 μm or less, 30 μm or more and 70 μm or less, or 40 μm or more and 60 μm or less. Preferably, the thickness of the polymer substrate may be 1 μm or more and 30 μm or less. More preferably, the thickness of the polymer substrate may be 5 μm or more and 15 μm or less, or 8 μm or more and 13 μm or less. By adjusting the thickness of the porous polymer substrate within the above range, the amount of active material contained in the electrochemical device can be increased by minimizing the volume of the electrochemical device while electrically insulating the positive and negative electrodes.

[0028] The porous polymer substrate may include pores having an average diameter of 0.01 μm or more and 1 μm or less. Specifically, the size of the pores included in the porous polymer substrate may be 0.01 μm or more and 0.09 μm or less, 0.02 μm or more and 0.08 μm or less, 0.03 μm or more and 0.07 μm or less, or 0.04 μm or more and 0.06 μm or less. Preferably, the size of the pores may be 0.02 μm or more and 0.06 μm or less. By adjusting the size of the pores of the porous polymer substrate within the above range, the air permeability and ionic conductivity of the entire manufactured separator may be controlled.

[0029] The air permeability of the porous polymer substrate can be 10 seconds / 100cc or more and 100 seconds / 100cc or less. Specifically, the air permeability of the porous polymer substrate can be 10 seconds / 100cc or more and 90 seconds / 100cc or less, 20 seconds / 100cc or more and 80 seconds / 100cc or less, 30 seconds / 100cc or more and 70 seconds / 100cc or less, or 40 seconds / 100cc or more and 60 seconds / 100cc or less. Preferably, the air permeability of the porous polymer substrate can be 50 seconds / 100cc or more and 70 seconds / 100cc or less. When the air permeability of the porous polymer substrate is within the above range, the air permeability of the manufactured separator can be provided within the range suitable for ensuring the output and cycle characteristics of the electrochemical device.

[0030] Air permeability (seconds / 100cc) means the time (seconds) taken for 100cc of air to pass through a porous polymer substrate or separator having a predetermined area at a constant pressure. Air permeability can be measured using an air permeability tester (Gurley Density Tester) according to ASTM D 726-58, ASTM D726-94, or JIS-P8117. For example, a Gurley 4110N Density Tester can be used to measure the air permeability of 100cc of air at a pressure of 0.304 kPa air or 1.215 kN / m 2 The pressure of water passing through 1 square inch (or 6.54 cm 2 ) sample. For example, the time it takes for 100cc of air to pass through a 1 square inch sample at a constant pressure of 4.8 inches of water at room temperature can be measured using an EG01-55-1MR tester from Asahi Seico Co., Ltd.

[0031] The porosity of the porous polymer substrate may be 10% by volume or more and 60% by volume or less. Specifically, the porosity of the porous polymer substrate may be 15% by volume or more and 55% by volume or less, 20% by volume or more and 50% by volume or less, 25% by volume or more and 45% by volume or less, or 30% by volume or more and 40% by volume or less. Preferably, the porosity of the porous polymer substrate may be 30% by volume or more and 50% by volume or less. When the porosity of the porous polymer substrate is within the above range, the ionic conductivity of the manufactured separator may be provided within a range suitable for ensuring the output and cycle characteristics of the electrochemical device.

[0032] Porosity means the ratio of the volume of pores to the total volume of the porous polymer substrate. Porosity can be measured using methods known in the art. For example, porosity can be measured using a BET (Brunauer Emmett Teller) measurement method using nitrogen adsorption, a capillary flow porometer, or a water or mercury permeameter.

[0033] The porous coating is formed on at least one surface of the porous polymer substrate and may include metal-organic framework particles and a polymer binder. The metal-organic framework particles may refer to a single type of metal-organic framework, or one or more metal-organic frameworks aggregated to form regular or irregular particles.

[0034] The metal-organic framework particles may include first metal-organic framework particles that are identical to each other but at least part of the surface is modified by polyimide and second metal-organic framework particles whose surface is not modified. Alternatively, the metal-organic framework particles may include two or more types of metal-organic framework particles that are different from each other, and the surface of any one of the particles may be modified by polyimide and the particle may be referred to as a first metal-organic framework particle.

[0035] The metal-organic framework particles may include one or more metal ions or metals including zirconium; and one or more organic ligands including ligands having amine groups. At least one of the organic ligands may include one or more amine groups and may coordinate with the metal ion or metal so that one or more amine groups are exposed to the surface of the metal-organic framework particles. For example, at least one of the first metal-organic framework particles and the second metal-organic framework particles includes zirconium and may have amine groups introduced therein. Preferably, both the first metal-organic framework particles and the second metal-organic framework particles include zirconium and have organic ligands including amine groups coordinated with zirconium.

[0036] The characteristic of metal-organic skeleton can be changed according to the type of functional group introduced, and in the metal-organic skeleton with the amine group introduced therein, the characteristic related to gas adsorption can be the most excellent.For example, compared with the metal-organic skeleton with the carboxyl group, sulfonic acid group or hydroxyl group introduced therein, the metal-organic skeleton with the amine group introduced therein has a larger specific surface area and pore size, so as to have excellent carbon dioxide adsorption capacity.In addition, because the amine group acts as a Lewis base center, compared with the metal-organic skeleton particles without the amine group, the metal-organic skeleton particles with the amine group have excellent adsorption capacity for carbon dioxide.Compared with the metal-organic skeleton with polar functional groups or hydrophobic functional groups, the metal-organic skeleton with the amine group can provide stable carbon dioxide adsorption capacity in the presence and absence of water.For example, compared with the metal-organic skeleton with the naphthyl group, nitro group or methoxyl group introduced therein, the metal-organic skeleton with the amine group introduced therein can provide stable adsorption capacity for carbon dioxide, because it can form hydrogen bonds with water or carbon dioxide by the amine group.

[0037] The surface of the first metal-organic framework particles is modified by polyimide. The first metal-organic framework particles can be amine metal-organic framework particles, and preferably, can have one or more amine groups exposed to the particle surface. The first metal-organic framework particles modified by polyimide can include those in which polyimide is formed by utilizing at least some of the amine groups in the imidization reaction, or those in which polyimide is introduced by the part other than the amine groups in the metal-organic framework. The first metal-organic framework modified by polyimide can have one or more amine groups exposed to the surface. Compared with unmodified particles, the first metal-organic framework particles modified by polyimide have excellent dispersibility and stability in the coating slurry for forming a porous coating. The coating slurry containing the first metal-organic framework particles modified by polyimide can have reduced precipitate generation and sedimentation velocity. The porous coating prepared with the coating slurry has a higher packing density per unit thickness, which can provide improved adsorption capacity of gases generated in electrochemical devices.

[0038] The average particle size (D) of the first metal-organic framework particles and the second metal-organic framework particles according to particle size distribution (PSD) analysis 50) can each be 300nm or more and 10μm or less. Specifically, the average particle size of each particle can be 300nm or more and 5000nm or less, 400nm or more and 2000nm or less, or 500nm or more and 1000nm or less. By adjusting the average particle size of the metal-organic skeleton particles within the above range, the specific surface area of ​​the porous coating is maximized, and therefore, a separator with excellent gas adsorption capacity can be manufactured. The first metal-organic skeleton particles modified by polyimide can have an average particle size larger than the second metal-organic skeleton particles. Specifically, the average particle size of the second metal-organic skeleton particles can be 300nm or more and 1000nm or less, and the first metal-organic skeleton particles can have a larger average particle size larger than the second metal-organic skeleton particles in the range of 300nm or more and 10μm or less.

[0039] Regarding the particle size distribution analysis, the average particle size of the particles can be obtained from the distribution of the particle settling velocity (separation velocity distribution) after the metal-organic framework particles are dispersed in the dispersion medium. For example, after one or more particles are dispersed in the dispersion medium, the light transmittance of the precipitated particles is measured at regular time intervals, and the average particle size of the particles can be obtained using the particle migration velocity obtained from the transmission curve and the absorbance of the corresponding particles of the maximum absorbance obtained by converting the transmittance into absorbance.

[0040] The average pore size of the first metal-organic framework particles and the second metal-organic framework particles can each be greater than 5nm and less than 200nm. Specifically, the average diameter of the holes formed in each particle can be greater than 5nm and less than 190nm, greater than 30nm and less than 180nm, greater than 50nm and less than 170nm, greater than 60nm and less than 160nm, greater than 70nm and less than 150nm, greater than 80nm and less than 140nm, greater than 90nm and less than 130nm, or greater than 100nm and less than 120nm. By adjusting the pore size of the metal-organic framework particles within the above range, the specific surface area of ​​the porous coating is maximized, and therefore, a separator with excellent gas adsorption capacity can be manufactured. The first metal-organic framework particles modified by polyimide can have an average pore size smaller than the second metal-organic framework. Specifically, the average pore size of the second metal-organic framework particles can be 35nm or more and less than 200nm, and the first metal-organic framework particles can have an average pore size smaller than the second metal-organic framework particles in the range of 5nm or more and less than 200nm. The average pore size of the first metal-organic framework particles can be 5nm or more and less than 50nm, preferably 7nm or more and less than 30nm.

[0041] The average pore size of the metal-organic framework particles may be a value measured in the process of calculating a BET model using a BET specific surface area analyzer. The pore volumes per unit mass of the first metal-organic framework particles and the second metal-organic framework particles may each be 0.2 cm 3 / g or more and 1.0cm 3 / g or less. Specifically, each particle may include 0.3cm 3 / g or more and 0.9cm 3 / g or less or 0.5cm 3 / g or more and 0.8cm 3 / g or less. By adjusting the pore volume of the metal-organic framework particles within the above range, the specific surface area of ​​the porous coating is maximized, and thus, a separator with excellent gas adsorption capacity can be manufactured. Compared with the second metal-organic framework particles, the first metal-organic framework particles modified by polyimide can have a smaller pore volume per unit mass. Specifically, the pore volume of the second metal-organic framework particles can be 0.8cm 3 / g or more and 1.0cm 3 / g or less, and the first metal-organic framework particles may have a diameter of 0.2 cm 3 / g or more and 1.0cm 3 The average pore size of the first metal-organic framework particles may be 0.2 cm 3 / g or more and 0.5cm 3 / g or less.

[0042] Similar to the measurement of porosity described above, the pore volume per unit mass of the metal-organic framework particles can be measured using methods known in the art.

[0043] The first metal-organic framework particle and the second metal-organic framework particle can be independently selected from UiO-66, UiO-67, NU-1002 and MOF-808. Specifically, the first metal-organic framework particle and the second metal-organic framework particle can be independently selected from UiO-66-NH2, UiO-67-NH2, NU-1002-NH2 and MOF-808-NH2. For example, the first metal-organic framework particle can be UiO-66-NH2 modified with polyimide, and even after modification, it can have one or more amine groups exposed to the surface, and the second metal-organic framework particle can be UiO-66-NH2.

[0044] The porous coating may include a first metal-organic framework particle modified by polyimide and a second metal-organic framework particle not modified by polyimide in a weight ratio of 35:65 to 45:55. Preferably, the porous coating may include a first metal-organic framework particle and a second metal-organic framework particle in a weight ratio of 35:65 to 40:60. The first metal-organic framework can improve the dispersibility of the coating slurry to improve the packing density of the porous coating, and the second metal-organic framework can improve the specific surface area of ​​the porous coating. When both the first metal-organic framework particle and the second metal-organic framework particle in the above-mentioned weight ratio are included, a separator having a porous coating with both high packing density and high specific surface area can be obtained. When the first metal-organic framework particle is included in an amount greater than the above-mentioned ratio, the porous coating has a reduced specific surface area, which may reduce the amount of gas adsorption of the separator.

[0045] The polymer binder may bind the first metal-organic framework particles, the second metal-organic framework particles, or the first metal-organic framework particles and the second metal-organic framework particles contained in the porous coating layer, and may provide bonding strength to the porous coating layer.

[0046] The polymer binder may include an acryl-based polymer binder, a fluorine-based polymer binder, or a combination thereof.

[0047] The acryl-based polymer binder may contain one or more monomers selected from the following as repeating units: (meth)acrylic acid, (meth)acrylic acid ester, propyl acrylate, isopropyl acrylate, n-butyl acrylate, isobutyl acrylate, n-pentyl acrylate, isopentyl acrylate, n-ethylhexyl acrylate, 2-ethylhexyl acrylate, 2-hydroxyethyl acrylate, methyl methacrylate, ethyl methacrylate, propyl methacrylate, isopropyl methacrylate, n-butyl methacrylate, isobutyl methacrylate, n-pentyl methacrylate, isopentyl methacrylate , n-hexyl methacrylate, n-ethylhexyl methacrylate, 2-ethylhexyl methacrylate, hydroxyethyl methacrylate, (meth)acrylonitrile, butyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, ethyl (meth)acrylate, methyl (meth)acrylate, n-propyl (meth)acrylate, isopropyl (meth)acrylate, tert-butyl (meth)acrylate, amyl (meth)acrylate, n-octyl (meth)acrylate, isooctyl (meth)acrylate, isononyl (meth)acrylate, lauryl (meth)acrylate and tetradecyl (meth)acrylate.

[0048] For example, the acryl-based polymer binder may include one or more selected from the group consisting of polyacrylic acid, methyl acrylate, ethyl acrylate, isopropyl acrylate, n-butyl acrylate, isobutyl acrylate, ethylhexyl acrylate, methyl methacrylate, styrene-butadiene rubber, nitrile rubber, acrylonitrile-butadiene rubber, and acrylonitrile-butadiene-styrene rubber.

[0049] The fluorine-based polymer binder can be a polymer binder based on polyvinylidene fluoride. For example, the fluorine-based polymer binder can be one or more selected from polyvinylidene fluoride, polyhexafluoropropylene, polytetrafluoroethylene, polyvinylidene fluoride-hexafluoropropylene (PVDF-HFP), polyvinylidene fluoride-trichloroethylene (PVDF-TCE) and polyvinylidene fluoride-chlorotrifluoroethylene (PVDF-CTFE), and specifically, can be a copolymer containing polyvinylidene fluoride.

[0050] The polymer binder may have a particle shape. For example, the polymer binder may have a spherical or elliptical shape, but the shape is not limited thereto. The average particle size (D 50 ) may be 100 nm or more and 500 nm or less. Specifically, the average particle size (D 50 ) may be 150 nm or more and 450 nm or less, 200 nm or more and 400 nm or less, or 250 nm or more and 350 nm or less. Preferably, the polymer binder may have an average particle size (D 50 ) is a spherical particle of 200 nm or more and 400 nm or less. By adjusting the particle size of the polymer binder particles within the above range, the migration path of lithium ions and the bonding strength of the porous coating layer to the porous substrate can be simultaneously ensured.

[0051] The metal-organic framework particles and the polymer binder may be included in a weight ratio of 80:20 to 95:5. The metal-organic framework particles include both the first metal-organic framework particles and the second metal-organic framework particles, and the weight ratio of the metal-organic framework particles and the polymer binder may be 85:15, 90:10 or 95:5. By adjusting the amount of the metal-organic framework particles and the polymer binder within the above range, the adhesion of the porous coating to the porous polymer substrate and the thermal shrinkage of the porous polymer substrate can be reduced.

[0052] The bulk density of the porous coating can be 1g / cm 3 or greater and 1.04g / cm 3 By adjusting the packing density of the porous coating layer within the above range, a separator showing stable cycle characteristics in terms of air permeability and electrical resistance can be obtained.

[0053] The porous coating can be formed by coating a surface of a porous polymer substrate with a coating slurry comprising a first metal-organic framework particle, a second metal-organic framework particle, a polymer binder and a dispersion medium. For example, the separator can be manufactured by coating the coating slurry on at least one surface of the porous polymer substrate and then drying the resulting material to remove the dispersion medium. The porous coating can have a porous structure by including a gap volume in which the first metal-organic framework particle, the second metal-organic framework particle, or the first metal-organic framework particle and the second metal-organic framework particle are connected by a polymer binder. The porous coating can adhere to the porous polymer substrate to prevent thermal shrinkage of the porous polymer substrate while allowing lithium ions to pass through.

[0054] The coating slurry includes a dispersion medium, so that at least a portion of the polymer binder is dissolved or dispersed, and the first metal-organic framework particles and the second metal-organic framework particles are dispersed. As a coating slurry, those in which the metal-organic framework particles are uniformly dispersed by controlling the type or content of the dispersion medium can be used. The first metal-organic framework particles can be modified by polyimide and show excellent dispersibility in the coating slurry. For example, the dispersion medium can be selected from one of water, ethanol, acetone, isopropyl alcohol (IPA), dimethylacetamide (DMAc), dimethylformamide (DMF), N-methyl-2-pyrrolidone (NMP), acetonitrile, and a combination thereof. By using the above-mentioned type of dispersion medium, a porous coating in which the first metal-organic framework particles and the second metal-organic framework particles are uniformly dispersed can be formed.

[0055] The viscosity of the coating slurry may be 20cps or more and less than 100cps. Specifically, the viscosity of the coating slurry may be 30cps or more and 90cps or less, or 40cps or more and 80cps or less. Preferably, the viscosity of the coating slurry may be 25cps or more and 40cps or less. When the viscosity of the coating slurry is 100cps or more, it becomes difficult to manufacture the separator by continuous coating on the porous polymer substrate, and productivity may not be ensured.

[0056] By further including additives such as dispersants, surfactants, defoamers, flame retardants and wetting agents, the coating slurry can improve dispersibility and flame retardancy, and improve the uniformity of the porous coating formed. For example, the dispersant can include one or more selected from oil-soluble polyamines, oil-soluble amine compounds, fatty acids, fatty alcohols, sorbitan fatty acid esters, tannic acid and pyrogallic acid. The use of the above-mentioned type of dispersant can improve the stability of the coating slurry, and can ensure the uniformity of the porous coating formed with the coating slurry.

[0057] Based on the total weight of the coating slurry, the additive may be included in an amount of 0 wt % or more and 5 wt % or less. Specifically, the additive may be included in an amount of 0.01 wt % or more and 4 wt % or less, 0.1 wt % or more and 3 wt % or less, or 1 wt % or more and 2 wt % or less. Preferably, the content of the additive may be 3 wt % or more and 5 wt % or less. By adjusting the content of the additive within the above range, uniform dispersion and stability of the first metal-organic framework particles and the second metal-organic framework particles contained in the coating slurry can be achieved.

[0058] The dispersion medium contained in the coating slurry can be removed by drying or heating after forming the porous coating. For example, the porous coating can contain the dispersion medium in an amount of 5ppm or less. Preferably, the porous coating can be formed by the first metal-organic framework particles, the second metal-organic framework particles and a polymer binder. During the process of removing the dispersion medium, a plurality of holes can be formed on the surface or inside the porous coating. The hole can include the gap volume formed between the first metal-organic framework particles, between the second metal-organic framework particles or between the first metal-organic framework particles and the second metal-organic framework particles, and can have a structure allowing fluid to pass through by forming a three-dimensional network.

[0059] The thickness of the porous coating layer may be 1 μm or more and 15 μm or less. Specifically, the thickness of the porous coating layer may be 2 μm or more and 14 μm or less, 3 μm or more and 13 μm or less, 4 μm or more and 12 μm or less, 5 μm or more and 11 μm or less, 6 μm or more and 10 μm or less, or 7 μm or more and 9 μm or less. Preferably, the thickness of the porous coating layer may be 1 μm or more and 5 μm or less. By adjusting the thickness of the porous coating layer within the above range, the shrinkage of the porous polymer substrate is minimized, and stable adhesion to the porous polymer substrate can be obtained.

[0060] The air permeability of the separator for electrochemical device can be 50 seconds / 100cc or more and 150 seconds / 100cc or less. Specifically, the air permeability of the separator can be 60 seconds / 100cc or more and 140 seconds / 100cc or less, 70 seconds / 100cc or more and 130 seconds / 100cc or less, 80 seconds / 100cc or more and 120 seconds / 100cc or less, or 90 seconds / 100cc or more and 110 seconds / 100cc or less. Preferably, the air permeability of the separator can be 50 seconds / 100cc or more and 80 seconds / 100cc or less. When the separator has an air permeability within the above range, the output, stability and cycle characteristics of the electrochemical device can be ensured.

[0061] Another embodiment of the present disclosure provides an electrochemical device, comprising: a positive electrode; a negative electrode; and a separator disposed between the positive electrode and the negative electrode, wherein the separator is a separator for an electrochemical device of the above embodiment. The electrochemical device can be manufactured by inserting an electrode assembly including a positive electrode, a negative electrode, and a separator disposed between the positive electrode and the negative electrode into a housing or a bag and sealing the housing or the bag. Before the housing or the bag is sealed, an electrolyte liquid can be injected to impregnate the electrode assembly with the electrolyte liquid. The shape of the housing or the bag is not limited. For example, the electrochemical device can be a cylindrical, prismatic, coin-type, or pouch-type lithium secondary battery.

[0062] The positive electrode and the negative electrode can be formed by coating the electrode active material on at least one surface of each current collector through coating and drying. As the current collector, a material having conductivity without causing chemical changes to the electrochemical device can be used. For example, the current collector for the positive electrode may include: aluminum; nickel; titanium; calcined carbon; stainless steel; aluminum or stainless steel whose surface is treated with carbon, nickel, titanium, silver, etc.; etc., but not limited thereto. For example, the current collector for the negative electrode may include: copper; nickel; titanium; calcined carbon; stainless steel; copper or stainless steel whose surface is treated with carbon, nickel, titanium, silver, etc.; etc., but not limited thereto. The current collector may have a variety of forms, such as thin metal plates, films, foils, meshes, porous bodies, and foams.

[0063] The positive electrode is provided with a positive electrode current collector and a positive electrode active material layer containing a positive electrode active material, a conductor and a binder resin on at least one surface of the current collector. The positive electrode active material may include one of the following: a layered compound or a compound substituted with one or more transition metals, such as lithium manganese composite oxide (LiMn2O4, LiMnO2, etc.), lithium cobalt oxide (LiCoO2) or lithium nickel oxide (LiNiO2); a lithium manganese oxide, such as Li 1+x Mn 2-x O4 (where x is 0 to 0.33), LiMnO3, LiMn2O3 or LiMnO2; lithium copper oxide (Li2CuO2); vanadium oxide, such as LiV3O8, LiV3O4, V2O5 or Cu2V2O7; 1-x M x Ni-site lithium nickel oxide represented by O2 (herein, M=Co, Mn, Al, Cu, Fe, Mg, B or Ga, and x=0.01 to 0.3); represented by the chemical formula LiMn 1-x M xA lithium manganese composite oxide represented by O2 (where M = Co, Ni, Fe, Cr, Zn or Ta, and x = 0.01 to 0.1) or Li2Mn3MO8 (where M = Fe, Co, Ni, Cu or Zn); LiMn2O4 in which some Li in the chemical formula is replaced by alkaline earth metal ions; a disulfide compound; and Fe2(MoO4)3, or a mixture of two or more types thereof.

[0064] The negative electrode is provided with a negative electrode current collector and a negative electrode active material layer containing a negative electrode active material, a conductor, and a binder resin on at least one surface of the current collector. As the negative electrode active material, the negative electrode may contain one type selected from the following: a lithium metal oxide; carbon such as non-graphitizable carbon or graphite-based carbon; Li x Fe2O3 (0 ≤ x ≤ 1); Li x WO2 (0 ≤ x ≤ 1); a silicon-based material such as Si, SiO x (0 < x < 2), SiC, and Si alloys; metal composite oxides such as Sn x Me 1- x Me' y O z (Me: Mn, Fe, Pb, Ge; Me': Al, B, P, Si, elements of Group 1, Group 2, and Group 3 of the periodic table, halogens; 0 < x ≤ 1; 1 ≤ y ≤ 3; 1 ≤ z ≤ 8); lithium metal; lithium alloy; tin-based alloy; metal oxides such as SnO, SnO2, PbO, PbO2, Pb2O3, Pb3O4, Sb2O3, Sb2O4, Sb2O5, GeO, GeO2, Bi2O3, Bi2O4, and Bi2O5; conductive polymers such as polyacetylene; Li-Co-Ni-based materials; and titanium oxides, or a mixture of two or more types thereof.

[0065] The conductor may be any one selected from graphite, carbon black, carbon fiber or metal fiber, metal powder, conductive whiskers, conductive metal oxides, carbon nanotubes, activated carbon, and polyphenylene derivatives, or a mixture of two or more types of these conductive materials. The carbon nanotube has a graphite sheet in a cylindrical shape with a nanometer-sized diameter and has sp 2Bonding structure, and according to the angle and structure of the graphite sheet rolling up, it shows the characteristics of a conductor or a semiconductor. Carbon nanotubes can be divided into single-walled carbon nanotubes (single-walled carbon nanotube, SWCNT), double-walled carbon nanotubes (doublewalled carbon nanotube, DWCNT) and multi-walled carbon nanotubes (multi-walled carbon nanotube, MWCNT) according to the number of bonds forming the wall, and these carbon nanotubes can be appropriately selected according to the application of the dispersion. More specifically, the conductor can be one selected from the following: natural graphite, artificial graphite, super p (super-p), acetylene black, Ketjen black, channel carbon black, furnace carbon black, lamp black, thermal cracking carbon black, denka black (denka black), aluminum powder, nickel powder, zinc oxide, potassium titanate and titanium oxide, or a mixture of two or more types of conductive materials in these.

[0066] As a binder resin, a binder resin commonly used in an electrode of an electrochemical device can be used. Non-limiting examples of such binder resins may include polyvinylidene fluoride-co-hexafluoropropylene, polyvinylidene fluoride-co-trichloroethylene, polymethyl methacrylate, polyethylhexyl acrylate, polybutyl acrylate, polyacrylonitrile, polyvinyl pyrrolidone, polyvinyl acetate, polyethylene-co-vinyl acetate, polyethylene oxide, polyarylate, cellulose acetate, cellulose acetate butyrate, cellulose acetate propionate, cyanoethyl pullulan, cyanoethyl polyvinyl alcohol, cyanoethyl cellulose, cyanoethyl sucrose, pullulan, carboxymethyl cellulose, etc., but are not limited thereto.

[0067] The electrolyte liquid is made of + B - A salt of the structure of is obtained by dissolving or dissociating in an organic solvent, wherein A + including alkali metal cations such as Li + 、Na + or K + , or a combination thereof, and B - Including anions such as PF6 - 、BF4 - , Cl - Br - ,I - 、ClO4 - 、AsF6 - 、CH3CO2 - CF3SO3 - 、N(CF3SO2)2 - or C(CF2SO2)3 -, or ions composed of a combination thereof, the organic solvent consists of: propylene carbonate (PC), ethylene carbonate (EC), diethyl carbonate (DEC), dimethyl carbonate (DMC), dipropyl carbonate (DPC), dimethyl sulfoxide, acetonitrile, dimethoxyethane, diethoxyethane, tetrahydrofuran, N-methyl-2-pyrrolidone (NMP), ethyl methyl carbonate (EMC), γ-butyrolactone, or a mixture thereof.

[0068] The electrochemical device including the electrode assembly may be a lithium secondary battery. The battery may be used as a unit cell, and may be used as a battery module including a unit cell, a battery pack including a battery module, and a device including a battery pack as a power source. The device may include small devices such as computers, mobile phones, and power tools; and medium to large devices powered by electric motors, such as electric motor vehicles including electric vehicles (EV), hybrid electric vehicles (HEV), plug-in hybrid electric vehicles (PHEV), etc.; electric two-wheeled bicycles including electric bicycles (E-bike) and electric scooters (E-scooters); electric golf carts; and systems for power storage, but not limited to these.

[0069] Another embodiment of the present disclosure provides a method for manufacturing a separator for an electrochemical device, the method comprising: forming a porous coating layer comprising first metal-organic framework particles modified with polyimide, second metal-organic framework particles, and a polymer binder on at least one surface of a porous polymer substrate. The description of the embodiment provided above replaces the content overlapping with the content described in the separator for an electrochemical device.

[0070] The step of forming the porous coating layer may include preparing a coating slurry including first metal-organic framework particles, second metal-organic framework particles, a polymer binder, and a dispersion medium, coating the coating slurry on the porous polymer substrate, and drying the resultant.

[0071] The step of forming the porous coating layer may further include a step of corona discharging at least one surface of the porous polymer substrate before coating the coating slurry on the porous polymer substrate. The step of corona discharging at least one surface of the porous polymer substrate prevents the reduction of the bonding strength between the surface of the porous polymer substrate and the surface of the coating layer at high temperature, and can prevent the reduction of the bonding strength between the surface of the polymer substrate and the surface of the coating layer caused by the electrolyte.

[0072] Corona discharge treatment can be for processing at least one surface of porous polymer substrate with 0.1kV or larger and 10kV or smaller voltage in air. Specifically, corona discharge treatment can be for processing with 0.2kV or larger and 9kV or smaller, 0.3kV or larger and 8kV or smaller, 0.4kV or larger and 7kV or smaller, 0.5kV or larger and 6kV or smaller, 0.6kV or larger and 5kV or smaller, 0.7kV or larger and 4kV or smaller, 0.8kV or larger and 3kV or smaller, 0.9kV or larger and 2kV or smaller, or 1.0kV or larger and 2kV or smaller voltage in air. Preferably, corona discharge treatment can be for processing with 1.8kV voltage in air. By adjusting the applied voltage of corona discharge treatment in the above range, a suitable number of functional groups are formed on the surface of polymer substrate, and surface damage to polymer substrate can be prevented.

[0073] The step of forming the porous coating layer can include coating the porous polymer substrate by applying the coating slurry on the porous polymer substrate. For example, the coating layer can be formed using methods such as a rod coater, a wire rod coater, a roller coater, a spray coater, a spin coater, an inkjet coater, a screen coater, a reverse coater, a gravure coater, a knife coater, a slot die coater, a hot melt coater, a comma coater, and a direct metering coater, but the method is not limited thereto. Preferably, the step of forming the porous coating layer can be to coat the coating slurry on both surfaces of the porous polymer substrate using a rod coater or a slot die coater.

[0074] The step of forming the porous coating layer may be to evaporate the dispersion medium contained in the coating layer by drying or heating the coating layer after applying the coating slurry on the porous polymer substrate. The removal of the dispersion medium may be performed at a temperature at which only the dispersion medium contained in the coating layer may be evaporated without deforming the polymer binder contained in the coating layer. For example, the removal of the dispersion medium may be to heat the coating layer at a predetermined temperature, but ensure that the temperature of the coating surface does not exceed 60°C. When the coating layer is heated under the above conditions, the thermal energy is first used to heat the dispersion medium and phase-change the dispersion medium, and may not be used to deform the polymer binder.

[0075] Hereinafter, the present disclosure will be described in more detail through specific embodiments and experimental examples. The following embodiments and experimental examples are only for illustrative purposes, and the present disclosure is not limited to the following embodiments and experimental examples.

[0076] Example 1

[0077] Preparation of coating slurry

[0078] As metal-organic framework particles, UiO-66-NH2 (average particle size (D 50 ): 1 μm, average pore size: 7 nm, pore volume: 0.8 cm 3 The first metal-organic framework particles modified with polyimide are prepared by reacting the amine groups on the surface of the metal-organic framework with the anhydride of polyimide.

[0079] An acryl-based polymer binder (Toyo Ink, Co., Ltd., CSB130, solid content 40%, average particle size (D 50 ) 177nm), carboxymethyl cellulose (GL CHEM, SG-L02) and a wetting agent, and introduced 12g of the first metal-organic framework particles modified by polyimide and 18g of the second metal-organic framework particles not modified by polyimide (the weight ratio between (the first metal-organic framework + the second metal-organic framework): the polymer binder is 95:5). The mixture is stirred for 60 minutes using an oscillator to prepare a coating slurry.

[0080] Preparation of porous polymer substrates

[0081] As the porous polymer substrate, a polyethylene film (MI: 0.2 g / 10 min, T m : 135°C, porosity: 45%, average pore size: 45nm).

[0082] Manufacturing of separators

[0083] The coating slurry was coated on both surfaces of the polyethylene film using a bar coater to form coating layers each having a coating thickness of 3 μm.

[0084] The process of removing the dispersion medium by applying a low-temperature air flow to the polyethylene film formed with the coating layer was repeated 5 times, and thus, a separator having a total thickness of 15 μm was manufactured.

[0085] Example 2

[0086] A separator was manufactured in the same manner as in Example 1, except that 10.5 g of the first metal-organic framework particles and 19.5 g of the second metal-organic framework particles were added when the coating slurry was prepared.

[0087] Comparative Example 1

[0088] A separator was manufactured in the same manner as in Example 1, except that 18 g of the first metal-organic framework particles and 12 g of the second metal-organic framework particles were added when the coating slurry was prepared.

[0089] Comparative Example 2

[0090] A separator was manufactured in the same manner as in Example 1, except that 9 g of the first metal-organic framework particles and 21 g of the second metal-organic framework particles were added when the coating slurry was prepared.

[0091] Comparative Example 3

[0092] A separator was manufactured in the same manner as in Example 1, except that 6 g of the first metal-organic framework particles and 24 g of the second metal-organic framework particles were added when the coating slurry was prepared.

[0093] Comparative Example 4

[0094] A separator was manufactured in the same manner as in Example 1, except that when the coating slurry was prepared, the first metal-organic framework particles were not used, and only 30 g of the second metal-organic framework particles were added.

[0095] Comparative Example 5

[0096] The separator was manufactured in the same manner as in Example 1, except that when the coating slurry was prepared, the first metal-organic framework particles and the second metal-organic framework particles were not used, and 30 g of alumina particles (Sumitomo, AES11, average particle size (D 50 )500nm, density 4g / cm 3 ).

[0097] Experimental example: Determination of separator characteristics

[0098] The characteristics of the separators produced in Examples and Comparative Examples were determined, and the results are shown in Table 1 below.

[0099] Measurement of sedimentation velocity of precipitates in coating slurries

[0100] The sedimentation rate of the precipitate in the coating slurry prepared in the process of manufacturing the separator of each embodiment and comparative example was determined. Since the metal-organic framework particles contained in the coating slurry have better dispersibility, the sedimentation rate of the precipitate is lower.

[0101] The sedimentation velocity of the precipitate in the coating slurry was determined using a LUMiSizer dispersion and particle size analyzer (LUM GmbH). The coating slurry was dispensed into the tube of the analyzer and a centrifugal force of up to 2,300 G was applied to accelerate the sedimentation or emulsification of the material in the tube. A transmission curve was obtained while continuously transmitting near-infrared light through the entire tube, and the sedimentation velocity of the precipitate was then calculated from the curve. The results are shown in Table 1 below.

[0102] Measurement of BET surface area

[0103] The adsorption isotherms were measured up to 1 bar at -196°C using a BET surface area analyzer (BEL, Microtrac GmbH) on the coating of each separator, and the BET surface area was calculated using the Brunauer-Emmett-Teller (BET) model from the measured N2 adsorption isotherm curves.

[0104] Measurement of CO2 adsorption by inorganic particles

[0105] An adsorption isotherm curve was measured using a BET specific surface area analyzer at 25° C. by permeating carbon dioxide having a purity of 99.99% through inorganic particles before preparing coating slurry for each separator, and the amount of carbon dioxide adsorbed relative to the weight of the inorganic particles was measured.

[0106] Method for obtaining data on CO2 gas quantity

[0107] The positive electrode was prepared by weighing a lithium manganese-based composite oxide, a conductive agent (Denka Black) and a binder (PVdF) in a weight ratio of 95:2.5:2.5, mixing them in N-methylpyrrolidone (NMP) to produce a positive electrode active material slurry, coating the slurry on a 20 μm thick aluminum foil at a thickness of 200 μm, and then rolling and drying.

[0108] A lithium metal plate having a thickness of 200 μm was used as the negative electrode, and after the positive electrode and the negative electrode were layered with the separator of the example or the comparative example interposed therebetween, the resultant was inserted into an aluminum bag.

[0109] 1 g of electrolyte liquid was injected into an aluminum bag, and the bag was sealed to manufacture a battery. The electrolyte liquid contained 3 mol of vinylene carbonate (VC) as an additive, 1.5 mol of propane sultone (PS), 1 mol of ethylene sulfate (ESa) and 1 mol of lithium salt LiPF6 in a solvent in which ethylene carbonate (EC) / ethyl methyl carbonate (EMC) were mixed in a weight ratio of 3 / 7.

[0110] The fabricated battery was charged and discharged once at 0.1 C in a voltage range of 3.0 V to 4.4 V in a chamber at 25° C., and 1.0 C charging and 1.0 C discharging were repeated 300 times.

[0111] The battery that had undergone 300 cycles was punctured to collect the gas within the battery, and then the amount of carbon dioxide contained in the gas was quantified using a flame ionization detector (FID) and a thermal conductivity detector (TCD).

[0112] [Table 1]

[0113]

Claims

1. A separator for an electrochemical device, the separator comprising: a porous polymer substrate; and a porous coating layer comprising first metal-organic framework (MOF) particles modified with polyimide, second metal-organic framework particles, and a polymer binder, and formed on at least one surface of the porous polymer substrate, At least one of the first metal-organic framework particles and the second metal-organic framework particles comprises zirconium and has an amine group introduced therein.

2. The separator for an electrochemical device according to claim 1, wherein the average particle size (D) of the first metal-organic framework particles and the second metal-organic framework particles according to a particle size distribution (PSD) analysis is 50 ) are each 300 nm or more and 10 μm or less. 3 . The separator for an electrochemical device according to claim 1 , wherein the average pore diameter of the first metal-organic framework particles and the second metal-organic framework particles is each greater than 5 nm and less than 200 nm.

4. The separator for an electrochemical device according to claim 1, wherein the pore volumes per unit mass of the first metal-organic framework particles and the second metal-organic framework particles are each 0.2 cm 3 / g or more and 1.0cm 3 / g or less. 5 . The separator for an electrochemical device according to claim 1 , wherein the first metal-organic framework particles and the second metal-organic framework particles are each independently selected from UiO-66-NH 2 , UiO-67-NH 2 , NU-1002-NH 2 , and MOF-808-NH 2 . 6 . The separator for an electrochemical device according to claim 1 , wherein the first metal-organic framework particles and the second metal-organic framework particles are included in a weight ratio of 35:65 to 45:

55. 7 . The separator for an electrochemical device according to claim 1 , wherein the metal-organic framework particles and the polymer binder are contained in a weight ratio of 80:20 to 95:

5.

8. An electrochemical device comprising: positive electrode; negative electrode; and A separator disposed between the positive electrode and the negative electrode, The separator is a separator for an electrochemical device according to any one of claims 1 to 7.

Citation Information

Patent Citations

  • Apparatus and method for generating virtual human interaction based on artificial intelligence

    KR1020230048993A